Christocracy as a Theological Foundation: An Analysis of Leadership Authority in the Presbyterian-Synodal System - Merry Deiby Oroh (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
The Presbyterian-Synodal system of church government is based on the ideal theological foundation of Christocracy, the confession that Christ is the sole Head of the Church who rules directly through His Word and Spirit. Theoretically, this model rejects hierarchy, affirms the parity of all ecclesiastical officers (ministers, elders, deacons) as servants, and views the local church council as a complete church (ecclesia completa). However, in historical and contemporary practice, a fundamental tension exists whereby this system consistently deviates into hierarchical and clerical practices. This deviation manifests as a hierarchy of office (clericalism) and a hierarchy of assemblies (Synod-centrism), where authority shifts from Christ to official figures and Synodal structures that are viewed as the "highest court." This article aims to analyze the fundamental causes of this authority shift. Using a qualitative library research method, the author conducts a systematic-theological, historical-critical, and comparative analysis of the works of Reformers (especially Calvin), historical church order documents, and contemporary case studies (such as in Malawi and GMIM). This study concludes that this authority shift stems from two primary factors: First, a "theological deficiency" in many church order documents, which fail to affirm Christ's rule "through His Word and Spirit," stating instead only His rule "through the ministry of officials," thus effectively equating official authority with Christ's authority. Second, the historical legacy of Scottish "national covenant" ecclesiology, which was historically intentionally designed with a centralized authority structure for "godly officials" to "rule over" a mixed populace. The author recommends that churches in this tradition revise their church orders to explicitly re-assert the supremacy of Christ's rule through His Word and Spirit over any human official or synodical authority.